Soraya Hernández - Tumor–Stroma Interactions Drive 3D Growth and Self-Organization in PDAC Spheroids: A Quantitative Study in Microfluidic Models. (Jornada de Jóvenes Investigadores del I3A, 2025)
Tumor–Stroma Interactions Drive 3D Growth and Self-Organization in PDAC Spheroids: A Quantitative Study in Microfluidic Models.